A preliminary study the future of cloud computing technology for education in the Philippines through Scenario Building - Hombrebueno, Edison G. (University of the Philippines Diliman, 2012)
Today, the economies of scale and other features of cloud computing are likely to mean an increasing shift away from institutionally-hosted services. In the study, cloud computing technology as the latest buzz in the ICT industry was placed in such context and its possible implications in the Philippine educational system were cited through scenario building. The objective of this paper is to study the impact of cloud computing on modern education with education institutions are under increasing pressure to find ways to offer rich, affordable services and tool. With this being said, scenario building exercise was conducted to identify alternative future scenarios of cloud computing technology in education and suggest possible policy implications. Scenarios show that educational institutions can use the cloud to deliver better services, even as they work with few resources. By sharing IT services in the cloud, educational institutions can outsource non-core services and concentrate on offering students, faculty and staff the essential tools to help them be competitive and succeed. Thus, it can be said that cloud computing can help communities and the nation itself to transform education.